Dynamic adaptive streaming over HTTP‐based 3D resource allocation algorithm. Issue 23 (24th October 2019) - Deng, Yujie; Xu, Zhan; Tian, Zhigang
Abstract : With the improvement of people's quality of life, the demand for three‐dimensional (3D) video has gradually grown in recent years. However, there are many challenges to providing high‐definition and high‐fidelity 3D video. One of the most difficult challenges for users to provide 3D video is a large amount of energy lost during 3D video transmission. In this study, the authors present a 3D resource allocation system architecture, which can effectively alleviate the problem of large transmission energy loss. They propose that multiple users in a small cell can share video resources in the downlink from the cloud to the client. In the cloud processing, multiple users can share part of the cloud computing work cycle. In the downlink, multiple users can share part of video resources. They presume that some share output bits can be multicast to overall users, and the other bits can be sent to every user in unicast. They model this and derive the simulation results. The simulation results show that the resource allocation scheme in this study achieves greater energy savings under certain conditions than the traditional case without sharing the resource.